Commentary [Research Highlights : Neurotrophic Factor Treatment of Neurological Disorders: The Benefits of a Pleiotropic Treatment Approach] - F. Muresanu, Dafin; Doppler, Edith; Novak, Philipp (CNS & Neurological Disorders - Drug Targets, 2011)
Neurotrophic factors are essential for the survival and differentiation of developing neurons and also for their protection and recovery under pathological conditions. Therefore neurotrophic factors are being considered as a crucial therapeutic strategy for neurological disorders such as dementia or stroke. Similar pharmacological effects have been shown for Cerebrolysin, a neuropeptide preparation used for the treatment of neurodegenerative and cerebrovascular disorders. Experimental studies have shown protective and restorative effects of Cerebrolysin after stroke by inhibition of calpain [1], stabilizing neuronal integrity [2] and reducing apoptotic cell death [3]. In dementia model systems Cerebrolysin modulates kinase activities, which results in decreased amyloid β-peptide deposition and tau protein phosphorylation [4,5]. Positive effects on synaptic density and neuronal cytoarchitecture correlate with improved cognitive and behavioral performance [6,7]. In addition, Cerebrolysin promotes neurogenesis, an important self-repair mechanism of the brain [8,9]. Clinical trials have consistently shown that Cerebrolysin is an effective treatment for patients suffering from dementia of different origin. In vascular dementia, Cerebrolysin improved cognitive deficits and global clinical impression, which correlated with improvements in electroencephalogram activities [10, 11]. In patients with mild to moderate Alzheimer's disease Cerebrolysin has been shown to significantly improve cognition and the overall clinical response up to three months after active treatment [12,13]. Beneficial effects were also reported in activities of daily living and in behavioral performance [12-15]. Due to the observed long-lasting treatment effects Cerebrolysin seems to delay disease progression, which is in line with its pleiotropic mode of action targeting different molecular pathways in this pathologic cascade. Direct comparison of Cerebrolysin with cholinergic treatment resulted in comparable clinical efficacy in mild to moderate Alzheimer's disease and synergistic treatment effects were observed by combining both treatment strategies [16]. Stroke trials with Cerebrolysin have shown accelerated improvement in global, neurological, and motor functions, cognitive performance and activities of daily living. Cerebrolysin was effective in both early and late hospitalization [17-19]. However, early treatment start resulted in a faster and more efficient recovery of impaired neurological functions. Cerebrolysin had a fast onset of action with significant treatment effects as early as the first days. Safety data from clinical trials suggest an excellent benefit-to-risk ratio. Cerebrolysin was safe and well-tolerated also in hemorrhagic stroke, permitting early initiation of treatment even when exact type of stroke is not yet known. Most importantly, Cerebrolysin was also safe when used in combination with recombinant tissue-type plasminogen activator without enhancing the number or severity of side effects resulting from recombinant tissue-type plasminogen activator treatment [Lang, manuscript in preparation] or when given in combination with cholinesterase inhibitors such as donepezil [16] or rivastigmine [20]. In conclusion, clinical data have strongly shown that Cerebrolysin is an effective therapeutic option for patients diagnosed with dementia, stroke or traumatic brain injury....